Analisis Pengaruh Dimensi Kualitas Jasa Terhadap Kepuasan Anggota Koperasi Pada Koperasi Nasib Di Butuh - Sri Nuryanto (JURNAL EKONOMI DAN TEKNIK INFORMATIKA, 2017)
This research aims is to examine: 1) Tangible toward the works’ satisfaction, 2) Reraliablelity toward the works’ satisfaction, 3) Responsiviness toward works’ satisfaction, 4) Assurance toward the works’ satisfaction, 5) Emphaty toward works’ satisfaction The data are collected from 60 respondens by using random sampling method. They are analyzed through the research instruments such as a product moment test and the reliability test by using a Cronbach Alpha tecnique; hypothesis test uses a path regression analysis. The research result shows that: 1) Tangible gives positive and significant influence toward the satisfaction of the staff of Koprasi Nasib Kecamatan Butuh Purworejo district, 2) Reablelity gives positive and significant influences toward the satisfaction of staff of Koprasi Nasib Kecamatan Butuh Purworejo district, 3), responsiviness gives positive and significant influences toward the satisfaction of the staff of Koprasi Nasib Kecamatan Butuh Purworejo district 4, Assurance gives positive and significant influence toward the satisfaction of the staff of Koprasi Nasib Kecamatan Butuh Purworejo district 5) Emphaty give positive and significant toward the satisfaction of the staff of Koprasi Nasib Kecamatan Butuh Purworejo district. The path regression analysis shows: that Tangible, Reraliablelity, responsiviness, and Assurance give influence positive and direct toward the satisfaction, otherwise Emphaty give influence negative and significan toward the satisfaction of staff of Koprasi nasib Kecamatan Butuh Purworejo district. Keywords: Tangible, Reablelity, Responsiviness, Assurance, Emphaty, and Satisfaction